Polo‐Like Kinase 2 is Dynamically Regulated to Coordinate Proliferation and Early Lineage Specification Downstream of Yes‐Associated Protein 1 in Cardiac Progenitor Cells. Issue 10 (24th October 2017) - Mochizuki, Michika; Lorenz, Vera; Ivanek, Robert; Della Verde, Giacomo; Gaudiello, Emanuele; Marsano, Anna; Pfister, Otmar; Kuster, Gabriela M.
Abstract : Background: Recent studies suggest that adult cardiac progenitor cells (CPCs) can produce new cardiac cells. Such cell formation requires an intricate coordination of progenitor cell proliferation and commitment, but the molecular cues responsible for this regulation in CPCs are ill defined. Methods and Results: Extracellular matrix components are important instructors of cell fate. Using laminin and fibronectin, we induced two slightly distinct CPC phenotypes differing in proliferation rate and commitment status and analyzed the early transcriptomic response to CPC adhesion (<2 hours). Ninety‐four genes were differentially regulated on laminin versus fibronectin, consisting of mostly downregulated genes that were enriched for Yes‐associated protein (YAP) conserved signature and TEA domain family member 1 (TEAD1)‐related genes. This early gene regulation was preceded by the rapid cytosolic sequestration and degradation of YAP on laminin. Among the most strongly regulated genes was polo‐like kinase 2 ( Plk2 ). Plk2 expression depended on YAP stability and was enhanced in CPCs transfected with a nuclear‐targeted mutant YAP. Phenotypically, the early downregulation of Plk2 on laminin was succeeded by lower cell proliferation, enhanced lineage gene expression (24 hours), and facilitated differentiation (3 weeks) compared with fibronectin. Finally, overexpression of Plk2 enhanced CPC proliferation and knockdown of Plk2 induced the expression of lineage genes. Conclusions: Plk2 acts as coordinator of cell proliferation and early lineage commitment in CPCs. The rapid downregulation of Plk2 on YAP inactivation marks a switch towards enhanced commitment and facilitated differentiation. These findings link early gene regulation to cell fate and provide novel insights into how CPC proliferation and differentiation are orchestrated.